Methods to assess the effect of meat processing on viability of Toxoplasma gondii: towards replacement of mouse bioassay by in vitro testing. Issue 5 (May 2020) - Opsteegh, Marieke; Dam-Deisz, Cecile; de Boer, Paulo; DeCraeye, Stephane; Faré, Andrea; Hengeveld, Paul; Luiten, Ruud; Schares, Gereon; van Solt-Smits, Conny; Verhaegen, Bavo; Verkleij, Theo; van der Giessen, Joke; et al.
Graphical abstract: Highlights: Cell culture proved promising as an alternative to mouse bioassay for Toxoplasma gondii. Propidium monoazide-PCR was insufficient to discriminate between viable and killed parasites. NaCl reduces the presence of viable T. gondii in meat products. In vitro methods are needed to allow extensive testing of meat processing methods. Abstract: Consumption of meat containing viable tissue cysts is considered one of the main sources of human infection with Toxoplasma gondii . In contrast to fresh meat, raw meat products usually undergo processing, including salting and mixing with other additives such as sodium acetate and sodium lactate, which affects the viability of T. gondii . However, the experiments described in the literature are not always performed in line with the current processing methods applied in industry. It was our goal to study the effect of salting and additives according to the recipes used by industrial producers. Mouse or cat bioassay is the 'gold standard' to demonstrate the presence of viable T. gondii . However, it is costly, time consuming and for ethical reasons not preferred for large-scale studies. Therefore, we first aimed to develop an alternative for mouse bioassay that can be used to determine the effect of processing on the viability of T. gondii tissue cysts. The assays studied were (i) a cell culture method to determine the parasite's ability to multiply, and (ii) a propidium monoazide (PMA) dye-based assay to selectively detect DNA from intact parasites. Processing experiments were performed with minced meat incubated for 20 h with low concentrations of NaCl, sodium lactate and sodium acetate. NaCl appeared to be the most effective ingredient with only one or two out of eight mice infected after inoculation with pepsin-digest of portions processed with 1.0, 1.2 and 1.6% NaCl. Results of preliminary experiments with the PMA-based method were inconsistent and did not sufficiently discriminate between live and dead parasites. In contrast, the cell culture method showed promising results, but further optimization is needed before it can replace or reduce the number of mouse bioassays needed. In future, standardised in vitro methods are necessary to allow more extensive testing of product-specific processing methods, thereby providing a better indication of the risk of T. gondii infection for consumers.